Understanding and Application of Accounting Information Systems and Financial Literacy as Determinants of Msme Performance - Indharrosa Atina Firdaus; Indri Kartika (Athallah Publishing Globalindo, 2026)
This study empirically examines the influence of accounting information system understanding, accounting information system implementation, and financial literacy on MSME performance. This study used a quantitative approach. The population consisted of MSMEs engaged in rattan production in Jepara Regency. A purposive sampling method resulted in a sample of 89 respondents. Data were obtained using a questionnaire and then analyzed using multiple linear regression using SPSS software. The research findings confirm that AIS understanding, AIS implementation, and financial literacy contribute positively and significantly to MSME performance. Mature understanding and the intensity of system operation have been shown to reduce financial management inefficiencies and strengthen the basis for business policy-making. Furthermore, strong financial literacy skills equip business owners with the capabilities to control cash flow dynamics, construct accountable financial reports, and formulate more precise financial conclusions. MSMEs need to commit to transforming their conventional bookkeeping models into technology-based systems, utilizing digital facilities and financial literacy provided by the government. The government needs intensive mentoring and regular training on digital accounting applications, as well as the provision of inclusive, affordable, and easy-to-understand digital infrastructure.